CONCEPTUAL METAPHORS OF “FAMILY” IN ENGLISH AND UZBEK: A COGNITIVE-LINGUISTIC CROSS-CULTURAL ANALYSIS - Komilov Shukurullo Abdurashidovich; N.N. Radjapov (Ta’limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2026)
Abstract: This article examines the conceptual metaphors of “family” in English and Uzbek through the framework of Conceptual Metaphor Theory (CMT) developed by Lakoff and Johnson (1980). By identifying and comparing the primary metaphorical models through which the family concept is structured in both languages — including FAMILY IS A TREE, HOME IS A CASTLE, OTA IS THE HEAD, and ONA IS SACRED GROUND — the study demonstrates that while some metaphorical mappings are universal, others are culturally specific and reflect fundamentally different orientations toward family structure, individual-collective relations, and religious grounding. The findings show that English family metaphors tend to emphasise growth, construction, and individual agency, while Uzbek family metaphors foreground sacred hierarchy, generational duty, and collective rootedness. The article contributes to cross-cultural cognitive linguistics, metaphor studies, and linguoculturology.